Medidas reológicas em pasta geopolimérica: efeito da geometria e protocolo de ensaio - Fensterseifer, Emilia Jarutais (2023)
Understanding and optimizing the rheological properties of cementitious materials allows us to determine and precisely adjust their workability. In addition, understanding its flow enables predicting the behavior of the material during its production process, such as pumping, extrusion, transport, mixing and launching, and even through 3D printing. Over the past few years, several studies have been carried out with the goal of understanding the effect of synthesis parameters and the use of different raw materials of geopolymeric binders on their behavior and rheological properties. However, it is necessary to identify the variability of the measurements (-if exists-) as a consequence of the application of different testing conditions, and thus, assessing the effect of synthesis conditions or production on the properties in fresh state. Therefore, considering that available standard that addresses rheological properties measurements from rotational rheological tests were not designed for geopolymeric systems, the present work aims to evaluate the effect of geometry and test parameters on the rheological behavior of a fly ash-based geopolymeric paste. For this purpose, the methodology adopted consists in the execution of rotational rheometry tests with different measurement systems (geometries), type of shear protocol, and the maximum shear rate applied. Were used two sets of parallel plates (with smooth and crosshatched surfaces), two concentric cylinders (with 24- and 26-mm diameters), and a four-blade vane spindle. The flow curves were obtained by continuous (ramp) and steps shear rate increments up to 100 or 300 s-1 . The results showed that reducing the ratio between the spindle and the container radii (Ri/Rο ratio) for coaxial geometries can induce wrong shear stress/shear rate calculations. Besides, the differences in the shear stress measured with ramp and steps protocols increased as the Ri/Rο ratio increased. It was identified that parallel plates required a ring to keep the paste between the plates during shearing. Finally, increasing the maximum shear rate applied reduced the yield stress and viscosity values, which is associated with an improved particle dispersion. Overall, we can conclude that the experimental setup must be carefully chosen considering the characteristics of the geopolymer evaluated, and preliminary tests are highly advised to support this choice.